2015
DOI: 10.1002/2015jd023863
|View full text |Cite
|
Sign up to set email alerts
|

Observation and simulation of lake‐air heat and water transfer processes in a high‐altitude shallow lake on the Tibetan Plateau

Abstract: Lakes are an important part of the landscape on the Tibetan Plateau. Most of the Plateau lakes' area has been expanding in recent years, but lake‐atmosphere energy and water interaction is poorly understood because of a lack of observational data and adequate modeling systems. Based on the eddy covariance observation over a high‐altitude shallow and small lake (the small Nam Co Lake) during an ice‐free period from 10 April to 30 August 2012, this study analyzes the lake‐air heat and water vapor turbulent trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 83 publications
5
91
1
Order By: Relevance
“…The monthly mean temperature difference peaked in November when the monthly H was the highest. The phenomenon with the higher daily mean T s compared with T a was also observed over a small lake next to the large Nam Co Lake in the observation period from April to September 2012 (Wang et al, 2015). Among lakes in other regions of the world, the lake surface persistently warmer than the air was observed in tropical and subtropical lakes.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The monthly mean temperature difference peaked in November when the monthly H was the highest. The phenomenon with the higher daily mean T s compared with T a was also observed over a small lake next to the large Nam Co Lake in the observation period from April to September 2012 (Wang et al, 2015). Among lakes in other regions of the world, the lake surface persistently warmer than the air was observed in tropical and subtropical lakes.…”
Section: Discussionmentioning
confidence: 74%
“…In lowlands, the long-lasting unstable boundary layer is more typical for tropical and subtropical lakes (Verburg and Antenucci, 2010) than for temperate and boreal lakes with strong seasonality (Long et al, 2007;Rouse et al, 2008), and implies strong effects on the energy transport from the lake surface. On the TP, a persistently unstable atmosphere has been observed over Ngoring Lake during the most part of the ice-free period , as well as over a small lake nearby Nam Co Lake (Wang et al, 2015). Wang et al (2015) analysed data from a single year, while study combined observations from two subsequent summers that started in the middle of June, missed the early open-water period immediately after the ice-off and only show the daily mean characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al (2015) analyzed two-year surface energy budgets during the ice-free period over Lake Ngoring in the northeast of the TP. Wang et al (2015) observed and modeled the interactions between a lake and the air during the summer over a small and shallow lake in the Nam Co basin of the central TP. Moreover, remote-sensing-based investigations have suggested that most lakes in the central TP have experienced significant expansions in area and increases in water level during the past few decades Wang et al 2013;.…”
Section: Introductionmentioning
confidence: 99%